An Investigation into business-to-business electronic commerce organizations - Lin, Chad; Pervan, Graham; Tsao, H.; Lin, K. (Australian Computer Society Inc., 2008)
The issue of information technology (IT) investment evaluation in B2BEC (business-to-business electronic commerce) has generated a lot of interest and discussion among academics and researchers. This research was undertaken to investigate the relationships between the level of IT maturity, the use of IT investment evaluation (IEM) and benefits realization (BRM) methodologies,and the degree of satisfaction with the adoption of B2BEC in Taiwanese B2BEC organizations. The results indicated that the level of IT maturity was a strong predictor of the use of evaluation methodologies while the use of evaluation methodologies had a significant impact on the degree of satisfaction with the adoption of B2BEC. It was also found that evaluation methodologies had played a mediating role between the level of IT maturity and the degree of satisfaction with the adoption of B2BEC. Managerial implications and future research directions are also provided. ACM Classifications: H.0. (Information Systems - General), K.6. (Computing Milieux - Management of Computing and Information Systems)